Analisis Hubungan Kuat Tekan Uniaksial dan Kuat Tarik Tidak Langsung dengan Metode Regresi pada Batupasir Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Muhlisin Efendi; Revia Oktaviani; Windhu Nugroho (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Rock strength has an important role in the mining industry. These forces can determine many aspects of mining such as slope geometry, excavation, blasting, and drilling. Rock strength can include tensile strength, compressive strength, and shear strength. In this case, the test is carried out to determine the correlation of uniaxial compressive strength and indirect tensile strength. The method used to determine the correlation of compressive strength and indirect tensile strength is by linear regression approach, which will then be analyzed for accuracy through Root Mean Square Error (RMSE), and Mean Absolute Percentage error (MAPE). This study used quantitative and qualitative methods, starting from the coordinate data of rock sampling locations, physical properties and mechanical properties. In this study, there were 6 sampling locations located in 2 different areas, namely Loa Janan and Sanga-sanga. The secondary data used are regional geological maps and maps of the area where the study is located. Furthermore, secondary data is processed using Arcgis software for mapping, and using Microsoft Excel software to assist in calculations in determining the value of physical and mechanical properties of rocks. The results of the compressive and tensile strength tests in this study showed a perfect corelation using linear regression, namely UCS= 3.9582 σt - 0.4004, with a correlation coefficient (R) of 0.972 and a determination coefficient (R2) of 0.945. and obtained RMSE 0.033 and MAPE 5.89%.